2018
DOI: 10.1088/1361-6463/aaaba8
|View full text |Cite
|
Sign up to set email alerts
|

Wave propagation and power flow in an acoustic metamaterial plate with lateral local resonance attachment

Abstract: This paper presents analysis on wave propagation and power flow in an acoustic metamaterial plate with lateral local resonance. The metamaterial is designed to have lateral local resonance systems attached to a homogeneous plate. Relevant theoretical analysis, numerical modelling and application prospect are presented. Results show that the metamaterial has two complete band gaps for flexural wave absorption and vibration attenuation. Damping can smooth and lower the metamaterial’s frequency responses in high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 17 publications
(18 reference statements)
0
6
0
Order By: Relevance
“…The vibration power flow of metamaterial plate was obtained by using the finite element method and the energy flow method, so as to reveal its vibration suppression mechanism. The lateral local resonance metamaterial structure proposed by Wang et al [48,49] can also suppress low frequency noise (see Figure 12). By analyzing the energy band structure diagram of the metamaterial, they found that the metamaterial plate could generate two low-frequency band gaps by the equivalent mass.…”
Section: Thin Film Acoustic Metamaterialsmentioning
confidence: 99%
“…The vibration power flow of metamaterial plate was obtained by using the finite element method and the energy flow method, so as to reveal its vibration suppression mechanism. The lateral local resonance metamaterial structure proposed by Wang et al [48,49] can also suppress low frequency noise (see Figure 12). By analyzing the energy band structure diagram of the metamaterial, they found that the metamaterial plate could generate two low-frequency band gaps by the equivalent mass.…”
Section: Thin Film Acoustic Metamaterialsmentioning
confidence: 99%
“…where F mn is the modal force. By using the orthogonality of trigonometric functions, multiplying cos(λ am x) cos(λ bn y) on both sides of Equation (17), and integrating in the area of (x, y) ∈ ([0, a] × [0, b]), F mn can be given by:…”
Section: Forced Response Of the Finite Lr Plate With Elastic Boundarymentioning
confidence: 99%
“…Wang et al [16] studied a homogeneous damped plate with parallel attached resonators on both surfaces, from which two band gaps were generated to improve the band-gap performance. Wang et al [17] investigated wave propagation and power flow in an acoustic metamaterial plate with a lateral local resonance attachment, where two band gaps can be formed by tuning the parameters of the vertical spring-mass and the lateral spring-mass. A chiral-lattice-based elastic metamaterial beam with multiple resonators was numerically and experimentally studied for the broadband vibration suppression by utilizing their individual band gaps by Zhu et al [18].…”
Section: Introductionmentioning
confidence: 99%
“…Phononic crystal, an artificial periodic material, has the ability to create a frequency band useful for applications such as acoustic and elastic waveguides [1][2][3], wave filters [4,5], vibration control [6][7][8], acoustic cloaks [9,10], acoustic topological insulators [11,12] and energy harvesting devices [13,14]. Generally, there are two types of mechanisms, namely, the Bragg scattering (BS) mechanism and local resonance mechanism for opening a band gap.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al [21] proposed a continuum beam resonator. Wang et al [6,22] created multi-flexural band gaps in a periodic beam by lateral resonators. Xiao et al [23] expand the application of the spring-mass resonators by attaching it on a thin plate and studying the bending wave propagation characteristics in different directions.…”
Section: Introductionmentioning
confidence: 99%